Analisis Pengaruh Kompetensi Aparatur, Etos Pelayanan Publik, Adaptasi Teknologi, dan Komunikasi Internal terhadap Keberhasilan Transformasi Polri - Syafruddin, Syafruddin; Sari, Shinta Novita (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of apparatus competence, public service ethos, technology adaptation, and internal communication on the success of police transformation. Police transformation requires strengthening human resources, technological innovation, and effective internal communication to ensure professional public service delivery. This study employs a literature review method, gathering data from journals, books, and research reports published in the last 10 years. Findings indicate that apparatus competence significantly enhances transformation effectiveness, as competent personnel are able to perform tasks professionally. Public service ethos also contributes positively, as a work culture emphasizing integrity and responsibility strengthens the police’s public image. Adaptation to modern technology accelerates reform processes, including management information systems and online services. Effective internal communication supports coordination and quick decision-making, facilitating smooth reform implementation. The study highlights the importance of HR development, technological innovation, and internal communication as pillars of successful police transformation. These findings are expected to serve as a reference for internal policy-making within the police organization to strengthen reform and organizational modernization, while improving public service quality.